Analisis Literatur terhadap Implementasi IoT dalam Manajemen Transportasi Publik - Sutrisno, Danang; Sulaiman, Han (LANCAH: Jurnal Inovasi dan Tren, 2025)
The application of the Internet of Things (IoT) in public transportation management plays a crucial role in enhancing efficiency, safety, and user experience. IoT technology enables transportation systems to leverage real-time data to optimize operations and provide better services to the public. This study aims to evaluate the contribution of IoT in public transportation through a review of existing literature and to identify the benefits and challenges of its implementation. The method used in this research is a systematic literature review, where various relevant sources are analyzed to gain a comprehensive understanding of IoT implementation in the transportation sector. The findings indicate that IoT plays a significant role in supporting real-time vehicle tracking, more efficient route management, and enhancing the passenger experience by providing access to up-to-date information. Furthermore, this technology helps predict passenger congestion and improve transportation scheduling, ultimately improving punctuality and reducing traffic congestion. The contribution of this research provides in-depth insights into the integration of IoT in public transportation systems to improve performance and user satisfaction. However, the study also highlights challenges that need to be addressed, such as high infrastructure development costs and data privacy issues. Therefore, close collaboration between the government, service providers, and the public is essential in designing solutions that can overcome these challenges. Future research is recommended to explore the long-term impacts of IoT implementation and users' perceptions regarding data privacy and security concerns.